MODIFIKASI LINGKUNGAN MIKRO MENGGUNAKAN SUNGKUP PLASTIK DAN MULSA TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH VARIETAS LEMBAH PALU PADA AGROEKOSISTEM LAHAN SAWAH - Muhammad Ansar; Bahrudin Bahrudin; Imam Wahyudi (Universitas Tadulako, 2013)
An experiment was conducted in July-November 2013 to study the effect of transparent plastic tunnel and mulch on the growth and production of Lembah Palu shallot variety. The experiment was arranged in Split Plot Design and the combination treatments were replicated thrice. The main plot was transparent plastic tunnel consisted of without transparent plastic tunnel and transparent plastic tunnel of 0.13 mm thick. The sub plot was kinds of mulch included without mulch, paddy straw and black plastic. The Anova was used to determine the effect of treatments, and the honestly significant different at α of 0.05 to examine the differences among the treatments. The use of transparent plastic tunnel combined with paddy straw mulch increased the diameter of leaf sheet. Single treatment of transparent plastic tunnel produced higher plant height, total leaf number, total tuber clump-1 and fresh tuber weight ha-1 than without the transparent plastic tunnel. The application of paddy straw mulch and black plastic mulch resulted in higher number and length of leaf sheet, and weight of fresh tuber clumb-1 of Lembah Palu shallot variety compared to that without the mulch. Key words : Growth and production, mulch, shallot, and transparent plastic tunnel.